Synergistic effect of externally solidified crystals and Fe-rich intermetallic on the fracture behavior of HPDC alloy - Huiting Zheng; Yuanhang Jiang; Fei Liu; Haidong Zhao (Journal of Materials Research and Technology, 2023)
The synergistic effect of externally solidified crystals (ESCs) and Fe-rich intermetallic on the fracture behavior of high pressure die casting Al–8Si-0.4 Mg–2Zn alloy was investigated using in-situ tensile test. The results revealed that the localized stress concentration during tensile test were significantly depended on the characteristic of ESCs and Fe-rich intermetallic. The crack preferentially initiated in the region where fine Fe-rich phase was surrounded by the clustered ESCs, this mainly attributed to the inconsistency of stress distribution in the clustered ESCs during tensile loading. Meanwhile, the primary Fe-rich phase with high aspect ratio is also beneficial to the crack initiation. The cracks were propagated both in the grain boundary and internal region of ESCs. The final fracture occurred in both the interfacial region between ESCs and other intermetallic and the internal region of ESCs.